Issues Relating Disaster to Journalism Education - Aryal, Deb Raj (Communication Journal, 2022)
Nepali newspapers manage to include disaster-related incidents with priority. A huge number of stories about calamities have got space on the front pages based on their gravity and worthiness. However, it is debatable whether they are fulfilling their social responsibility. A reply to this question can make a huge commitment to overseeing tough spots connected with disasters. Journalism is expected to make it easier to deal with issues that arise before and after disasters. This necessitates that journalists comprehend the various tangents (distribution, causes, effects, ramifications, and possibilities) of disasters. In like manner, the debacle ought to be consolidated in news coverage and schooling so our reporting practice could contribute to that.